Genocide and political groups - Nersessian, David L., 1969- (Oxford : Oxford University Press, 2010)
During the drafting of the Genocide Convention in 1948, a critical and controversial decision was made to exclude political groups, thereby limiting the Convention to national ethnic, racial and religious collectives. This book analyzes whether this legal dichotomy continues to make sense.
Description based on online resource; title from PDF title page (viewed on Sept. 7, 2010).
Includes bibliographical references and index.
Keywords: Convention on the Prevention and Punishment of the Crime of Genocide -- (1948); Genocide -- Political aspects; Genocide